Elaboração e validação do questionário sobre qualidade de vida de atletas (QQVA) - Renata de Andrade Cunha (2008)
The sport can cause damages to the quality of life of athletes due to physical, psychological and social imbalances caused by factors such as injuries, excessive number of training and competitions and excessive nervousness during the competitions. The purpose of this study was to construct and validate an instrument to measure the perception of quality of life of Brazilian athletes of both genders and different individual and collective sports, the Questionnaire on Quality of Life for Athletes. The sample was composed of 298 athletes, with 179 men (60,1%) and 119women (39,9%). The mean age was 16,53 ± 1,74 years. The athletes belong to 12 different sports: swimming, basketball, futsal, soccer, handball, taekwondo, tennisfield, volleyball, fencing, archery, cycling and athletics. The selection of items of the instrument was based on literature review of quality of life, in the Theory of Action and in the questionnaire and the concept of quality of life of the World Health Organization (WHOQOL-100). The Content Validity Coefficient of the instrumentobtained by the evaluation of judges for the clarity of language and the practical pertinence were, respectively, 0,9509 and 0,9214. The factor analysis using the method of principal components and orthogonal Varimax rotation found a final solution of 14 items grouped into five factors, unlike the three theoretical dimensions (biological, psychological and social) in which the judges were asked to classify the items. The KMO index was 0,723 and the test of sphericity of Bartlett showed thatthere are significant correlations (p = 0,000) among the items. The commonalities showed values between 0,644 and 0,838. The items had factorial loads between 0,754 and 0,898 with the factor in which were grouped and factorial loads lower than 0,280 with other factors. The total explained variance was 74,060%. The internal consistency measured by the Cronbach's Alpha was 0,733 (general instrument), 0,855 (Signs and Symptoms of Overtraining Factor), 0,820 (Basic Conditions for Health Factor), 0,723 (Social Relationship in Sports Environment Factor), 0,793(Emotional States of the Athlete Factor) and 0,757 (Planning and Periodization of Sportive Training Factor). The instrument can be considered valid and reliable for assessing the perception of the quality of life for athletes.